Alopecia Fibrosante em Padrão de Distribuição Androgenética: Patogénese, Diagnóstico e Tratamento - Ana Marcos-Pinto; G. De Caprio; R. Oliveira Soares (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Fibrosing alopecia in a pattern distribution is a recently recognized type of scarring alopecia, with hair loss in androgens- dependent area. Loss of follicular openings, perifollicular erythema, perifollicular hyperkeratosis and anisotriquia are the trichoscopic clues and follicular lichenoid inflammatory infiltrate the important finding in histopathology. It shares features of androgenetic alopecia and lichen planopilaris. Dermatologists should be familiarized with this entity in order to optimize the diagnosis and provide early treatment to prevent irreversible follicular damage.